2005
DOI: 10.1093/chemse/bji015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Two Human Olfactory Receptors Expressed in the Baculovirus Sf9 Insect Cell System

Abstract: Olfactory receptors (ORs) are the largest member of the G-protein-coupled receptors which mediate early olfactory perception in discriminating among thousands of odorant molecules. Assigning odorous ligands to ORs is a prerequisite to gaining an understanding of the mechanisms of odorant recognition. The functional expression of ORs represents a critical step in addressing this issue. Due to limitations in heterologous expression, very few mammal ORs have been characterized, and so far only one is from human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Experimentally, heterologous expression of a FLAG (DYKDDDDK polypeptide sequence) tagged receptor in insect cells confirmed an extracellular N-terminus 29 . This leads us to conclude that hOR17-210 is missing both the first and second TMs when compared to other mammalian ORs.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Experimentally, heterologous expression of a FLAG (DYKDDDDK polypeptide sequence) tagged receptor in insect cells confirmed an extracellular N-terminus 29 . This leads us to conclude that hOR17-210 is missing both the first and second TMs when compared to other mammalian ORs.…”
Section: Resultsmentioning
confidence: 78%
“…This genomic pseudogene sequence was identified earlier as possessing a two-nucleotide frame shift 28 . A cDNA clone of this frame-shifted sequence was subsequently shown to successfully initiate a G-protein mediated signal transduction cascade in the presence of a mixture of odorants (especially ketone compounds 29 ) commonly perceived by humans.…”
Section: Gtp-binding Protein Coupled Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the region of TM2 correctly predicted as a helical TM region for rat I7 is not predicted as a TM in hOR17-210 despite the apparent sequence similarities. Experiments showed that this region was indeed extracellular and not a TM 29 .…”
Section: Tagtaggtgtagtaaagttgataatgaaatatcactctaaa Tcagtgg Cttaamentioning
confidence: 95%
“…The sequence in entry AAC99555, when directly translated yields the functional OR. The bolded region in Figure 1c shows the cDNA cloned protein sequence that was used in our analysis and in the experimental functional studies 29 .…”
Section: Tagtaggtgtagtaaagttgataatgaaatatcactctaaa Tcagtgg Cttaamentioning
confidence: 99%